Methodical instructions for control work on the discipline "First emergency premedical aid in emergency situations" - Tverdokhliebova, Natalia Yevgeniivna (Національний технічний університет "Харківський політехнічний інститут", 2024)
The discipline "First emergency premedical aid in emergency situations" is an integral part of the educational and professional program for bachelors in the specialty 263 - "Civil Security". The purpose of the discipline is theoretical and practical training of students to provide first aid to the affected population in emergency situations.
Keywords: first premedical aid; urgent actions; emergency; methodical instructions; control work